Sistematización del uso de fármacos sysadoa como alternativa terapéutica de la osteoartritis: un análisis conforme a las directrices prisma - Villarroel Castillo, Victoria Pamela (2025)
Introduction: Osteoarthritis is a joint disease of degenerative progression; the most common signs include joint pain being the early and common indicator SYSADOA drugs are shown as an attractive pharmacological alternative. Objective: To analyze the efficacy of using SYSADOA drugs as a therapeutic alternative for osteoarthritis through a systematic review according to PRISMA 2020 guidelines. Methodology: Both quantitative and qualitative study results from randomized controlled trials, randomized controlled crossover studies and open clinical trials published from 2019 to 2024 were included, the study was based on a non-experimental design, focused on a systematic theoretical analysis, The risk of bias of each study was assessed using the Cochrane collaboration tool and the GRADE system was used using the PRISMA 2020 methodology. Results: Chondroitin sulfate (CS) and glucosamine sulfate (GS) showed greater efficacy and safety against the other drugs belonging to the SYSADOA group, while diacerein despite significantly reducing pain presented less drug safety with more adverse effects.